Kinerja Keuangan Perusahaan Sebelum dan Selama Pandemi Covid-19 - Annisa Nur Faiqoh; Asri Nur Wahyuni (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2023)
The impact of the Covid-19 pandemic can be felt in all aspects. Not only the transportation sector, manufacturing and the economy, almost all sectors are affected, including the tourism sector which has been affected by the outbreak of Covid-19. The pressure is the significant drop in international visitor numbers with mass cancellations and shrinking bookings. This study aims to compare the company's financial performance before and during the covid-19 pandemic. 17 companies listed on the Indonesia Stock Exchange between 2018-June 2021 were selected for this study. The Wilcoxon Signed Rank Test and Paried Sample T-Test techniques were used as analytical tools to answer all the problems. The ratios using the Wilcoxon signed rank test were CR, NPM and PER. While the ratio that uses the Paried Sample T-Test is DAR. The results showed that differences in the company's financial performance before and during the covid-19 pandemic by using financial ratios.